Camphorpyrazolium-based chiral functional ionic liquids - Pastran, Jesus; Agrifoglio, Giuseppe; Gonzalez, Teresa; Briceno, Alexander; Dorta, Romano (Tetrahedron-Asymmetry, 2014)
The solvent-less quaternization of N-phenyl-camphorpyrazole 4 with BrC4H9,IC2H4OCH3, and IC2H4OC2-H4OC4H9 afforded the corresponding chiral pyrazolium halides 5a, 6a, and 7a in excellent yields. The anions were modified either by trihalide formation with Br-2 and 12, or by salt metathesis with LiNTf2 and NaCo(CO)(4). All pyrazolium salts bearing the di-ether side chain 7a-d were liquids at room temperature, while the X-ray crystal structure of the bis(trifluoromethylsulfonyl)amide salt of the corresponding mono-ether analogue 6c (mp 97 degrees C) revealed intermolecular H-bonding interactions. Furthermore, an improved protocol for the well-known but notoriously low-yielding synthesis of (+)-hydroxymethylene-camphor 3 is disclosed. (C) 2014 Elsevier Ltd. All rights reserved.